Assessment of smile esthetics and various types of face profiles - Janošević Predrag N.; Janošević Mirjana Lj; Perović Tatjana M.; Stojković Branislava B.; Stojanović Simona M. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2020)
Background: Imperfect smile and face profile is one of the main reasons why patients turn to orthodontists. Aim was to investigate if there is a difference in perception of smile and profile esthetics between the examined groups. Subjects and method: In conducted research, smiles of 21 persons (8 male and 13 female), 18 to 30 years old were evaluated by 15 orthodontists, 15 students of dentistry and 15 laypeople. They were to rate esthetics of every smile from 1 to 9 and choose just one main reason that impairs aesthetics. Orthodontists and laypeople should also evaluate male and female normal, bimaxillary prognathic and bimaxillary retrognathic profiles from 1 to 3. The most beautiful profile should be marked with number 3. Results: Although there was no statistically significant difference in the evaluation of smile esthetics among groups, laypeople gave the lowest evaluation. Apart from irregular position of certain teeth, all investigated groups emphasized different factors that impair smile esthetics. Orthodontists and laypeople marked bimaxillary prognathic male and female profile as less beautiful than the others. Conclusion: Because of the differences in perception of the smile aesthetics between orthodontists and laypeople, it is necessary to create a new diagnostic plan of treatment protocols that includes studies investigating laypeople perception of smile and facial esthetics.